Analisis Determinan Akuntabilitas Pengelolaan Keuangan Daerah (Studi empiris pada SKPD Pemerintah Kabupaten Kepulauan Talaud) - Aimbu, Lesli L; Saerang, David P E; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. The phenomenon can be observed in the development of the public sector today is the rise of increasingly demands to implement public accountability by public sector organizations (such as: the Central Government and the regions, Government work units, departments and State agencies). Public sector accountability demands are related to the necessity of conducting transparency and providing information to public, in order to fulfill the rights of the public. This research aims to analyze the variables of transformational leadership style, the competence of human resources (HR), organizational commitment, the use of management information systems area (SIMDA) finance and financial reporting against accessibility accountability financial management areas. The population in this research is financial management officers in Talaud Islands Regency SKPD. 175 respondents were taken to answer questionnaires in order to test the hypothesis and to know the influence of transformational leadership style, the competence of human resources (HR), organizational commitment, the use of Financial SIMDA and the accessibility of financial reports towards the accountability of financial management. F test and t-test analysis were conducted by using multiple linear regression. Â Results show that transformational leadership style, the competence of human resources (HR), organizational commitment, the use and accessibility of Finance SIMDA financial report simultaneously, positively and significantly influence the regional financial management accountability. On the other hand, transformational leadership style, the competence of human resources (HR), the use of financial SIMDA and the accessibility of financial report positively and significantly influence the accountability of financial management. Nevertheless, organisatonal commitment does not positively influence the accountability of financial management. Keywords: transformational leadership style, the competence of human resources (HR), organizational commitment, the use of Financial SIMDA and the accessibility of financial reports, the accountability of financial management Abstrak. Fenomena yang dapat diamati dalam perkembangan sektor publik dewasa ini adalah semakin menguatnya tuntutan pelaksanaan akuntabilitas publik oleh organisasi sektor publik (seperti: pemerintah pusat dan daerah, unit-unit kerja pemerintah, departemen dan lembaga negara). Tuntutan akuntabilitas sektor publik terkait dengan perlunya dilakukan transparansi dan pemberian informasi kepada publik dalam rangka pemenuhan hak-hak publik. Penelitian ini bertujuan untuk menganalisis variabel gaya kepemimpinan transformasional, kompetensi Sumber Daya Manusia (SDM), komitmen organisasi, penggunaan Sistem Informasi Manajemen Daerah (SIMDA) Keuangan dan aksesibilitas laporan keuangan terhadap akuntabilitas pengelolaan keuangan daerah. Populasi pada penelitian ini adalah pejabat yang terkait dengan proses pengelolaan keuangan daerah di SKPD Kabupaten Kepulauan Talaud yaitu sebanyak 175 orang dan metode sensus dilakukan untuk mengambil sampel, sehingga banyaknya sampel sama dengan jumlah populasi yaitu sebanyak 175 orang untuk menguji hipotesis gaya kepemimpinan transformasional, kompetensi Sumber Daya Manusia (SDM), komitmen organisasi, penggunaan SIMDA Keuangan dan aksesibilitas laporan keuangan terhadap akuntabilitas pengelolaan keuangan daerahÂ  secara bersama-sama dengan Uji F dan sendiri-sendiri digunakan dengan Uji t menggunakan metode analisis linier berganda dengan aplikasi SPSS. Hasil penelitian membuktikan bahwa secara bersama-sama gaya kepemimpinan transformasional, kompetensi Sumber Daya Manusia (SDM), komitmen organisasi, penggunaan SIMDA Keuangan dan aksesibilitas laporan keuangan berpengaruh positif dan signifikan terhadap akuntabilitas pengelolaan keuangan daerah. Secara parsial gaya kepemimpinan transformasional, kompetensi Sumber Daya Manusia (SDM), penggunaan SIMDA Keuangan dan aksesibilitas laporan keuangan berpengaruh positif dan signifikan terhadap akuntabilitas pengelolaan keuangan daerah. Sedangkan komitmen organisasi tidak berpengaruh positif terhadap akuntabilitas pengelolaan keuangan daerah. Kata Kunci : Gaya kepemimpinan transformasional, kompetensi Sumber Daya Manusia, komitmen organisasi, penggunaan SIMDA Keuangan dan aksesibilitas laporan keuangan, akuntabilitas pengelolaan keuangan daerah.Â